FISHERY OF JUVENILES OF PENAEUS SEMISULCATUS ALONG THE TINNEVELLY COAST, TAMIL NADU - Manissery, Mary K (Indian Journal of Fisheries, 2011)
Penaeus semisulcatus de Haan contributes to a considerable fishery on thesoutheast coast of India, particularly in the Gulf of Mannar. Juveniles occur inlarge concentrations in the shallow inshore sea, between Pattanamarudur and Tuticorin,covering a coastline of about 20 km. They are fished throughout the yearby an indigenous gear known as 'Ola Valai' operated in the waters within 2 mdepth; landing about 57 tonnes in 1978-79. The peak abundance was in November-January and June-July. The size ranged from 40 mm to 150 mm total length,majority measuring less than 100 mm, indicating that this area is a nursery groundof the species.